Investigating the diameter-dependent stability of single-walled carbon nanotubes. - Warner, J; Schäffel, F; Zhong, G; Rümmeli, M; Büchner, B; Robertson, J; Briggs, G (2009)
We investigate the long-standing question of whether electrons accelerated at 80 kV are below the knock-on damage threshold for single-walled carbon nanotubes (SWNTs). Aberration-corrected high-resolution transmission electron microscopy is used to directly image the atomic structure of the SWNTs and provides in situ monitoring of the structural modification induced by electron beam irradiation at 80 kV. We find that SWNTs with small diameters of 1 nm are damaged by the electron beam, and defects are produced in the side walls that can lead to their destruction. SWNTs with diameters of 1.3 nm and larger are more stable against degradation, and stability increases with diameter. The effect of diameter, defects, and exterior contamination on the inherent stability of SWNTs under electron beam irradiation is investigated.